Analisis Risiko Konstruksi Pada Proyek Pembangunan Gedung Citimall Garut - Irsal Adil Ahkop; Ganjar Jojon Johari; Adhitya Surya Pratama (Jurnal Konstruksi, 2025)
The development of facilities and infrastructure in Indonesia is experiencing quite significant progress, as seen from the large number of infrastructure/buildings built in various sectors. In addition to cost efficiency and time effectiveness, one indicator of the success of a construction project is the absence of work accidents during the construction process. This study focuses on the analysis of construction risks in the Citimall Garut building construction project. The purpose of this study is to identify risks, determine the level of risk (low-medium-high), and to determine the appropriate dominant medium risk response in the Citimall Garut Building construction project. In this study, a qualitative descriptive method was used. The methods used in this study, namely the Severity Index and Probability Impact Matrix, are very relevant to other construction projects. The application of this method to similar projects will help in early risk identification and the preparation of more appropriate mitigation strategies. Prioritize risk management according to the severity and likelihood of occurrence. The results of the study of Construction Risk Analysis in the Citimall Garut Building Construction Project, there are 17 valid risk variables for the project. 3 medium category risks that affect costs, 6 medium category risks that affect time. The most dominant risk that occurs in the cost aspect is damage to project equipment and machinery, while from the time aspect is changes to the work schedule. The response to the risk of changes to the work schedule is to create a project schedule that has a buffer time to anticipate potential changes or delays. This includes including reserve time in the schedule for critical tasks. The response to the risk of damage to project equipment and machinery is to carry out routine maintenance on all project equipment and machinery to prevent damage. Preventive maintenance can include periodic inspections, lubrication, and replacement of worn-out spare parts before damage occurs.